Chapter 38: Strawberry Production in Florida - Natalia A. Peres; James F. Price; William M. Stall; Craig K. Chandler; Stephen M. Olson; Timothy G. Taylor; Scott A. Smith; Eric H. Simonne (EDIS)
This document is HS736, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.